Paraproteinemic neuropathies. Issue 1 (22nd November 2014) - Raheja, Divisha; Specht, Charles; Simmons, Zachary
ABSTRACT The paraproteinemias are a heterogeneous group of disorders in which monoclonal plasma cells cause the proliferation of monoclonal proteins. They are of importance to clinicians because they often occur in association with neuropathies. Neurologists play a particularly important role when the neuropathy is the presenting feature, in which case they may uncover clinical, laboratory, radiologic, electrodiagnostic, or biopsy findings that lead to identification of the underlying paraproteinemia. The frequency of neuropathies in these patients, and the extent to which such neuropathies dominate the clinical picture, varies significantly between the different paraproteinemias. Treatments may be aimed specifically at the neuropathy, or against the underlying hematologic disorder. In all patients with paraproteinemias, the neurologist can work collaboratively with the hematologist to formulate therapeutic plans and goals and can provide follow‐up and monitoring to determine the response of the neuropathy to treatment. Muscle Nerve51: 1–13, 2015